1977
DOI: 10.1002/1097-0142(197711)40:5<2381::aid-cncr2820400555>3.0.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

Psychological and social adjustment to mastectomy.A two-year follow-up study

Abstract: A consecutive series of 160 women admitted to hospital for breast tumor biopsy was assessed prior to, and at 3, 12, and 24 months following operation for marital, sexual, interpersonal and work adjustment, depression, and personality characteristics by means of rating scales based on structures interviews and standard tests. By 2 years there wery no significant differences in social adjustment between mastectomy patients and benign breast disease controls; 70% of cancer patients were no longer stressed by mast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
130
1
6

Year Published

1990
1990
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 427 publications
(140 citation statements)
references
References 8 publications
3
130
1
6
Order By: Relevance
“…A study conducted by Morris et al indicated that two main issues affect breast cancer patients' sexuality after surgical treatment: personality and psychological factors. They found that clinical factors did not predict quality of sexual life, sexual functioning or sexual enjoyment (Morris et al, 1977). Depression and anxiety in women are often associated with an increase in female sexual dysfunction and an increase in marital discord.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted by Morris et al indicated that two main issues affect breast cancer patients' sexuality after surgical treatment: personality and psychological factors. They found that clinical factors did not predict quality of sexual life, sexual functioning or sexual enjoyment (Morris et al, 1977). Depression and anxiety in women are often associated with an increase in female sexual dysfunction and an increase in marital discord.…”
Section: Discussionmentioning
confidence: 99%
“…On general measures of psychological adjustment and quality of life, it is often found that cancer patients are indistinguishable from the general population by 1 or 2 years after diagnosis, given that treatment is complete and the cancer controlled. [3][4][5][6][7] Within this context of overall positive adjustment, however, two points deserve mention. First, there is substantial variability in adjustment.…”
mentioning
confidence: 99%
“…(Millar et al, 2005) In other studies, this trait also in part explained the variance in depressive symptoms after breast cancer surgery (Den Oudsten et al, 2009a, Golden-Kreutz andAndersen, 2004), as well as of poor adjustment to mastectomy. (Morris et al, 1977) After discussing the results of the study, certain limitations and strengths should be acknowledged. Strength of the underlying study is the baseline measurement, before the diagnosis is known.…”
Section: Discussionmentioning
confidence: 99%